Prevalence and risk factors for permanent cerebrospinal fluid diversion in children after posterior fossa tumor surgery - ควรสนธิ ภัทร; บุณยะรัตเวช กฤษณพันธ์ (Thai Journal of Neurological Surgery, 2025)
Objectives: Posterior fossa tumors are common in children, which are prone to cause disturbances of cerebrospinal fluid (CSF) dynamics. Approximately 15.5-40% of patients require CSF diversion procedure after tumor resection. The incidence of postoperative ventriculoperitoneal (VP) shunt in children after posterior fossa tumor surgery in Thailand has not been described and the risk factors are poorly understood. The authors, therefore, conducted a study to identify the risk factors for postoperative VP shunt Material and methods: The authors retrospectively reviewed data of the patients who underwent surgery for posterior fossa tumor between January 2002 and August 2019. The potential factors for postoperative VP shunt were collected included age at time of surgery, sex, the use of pre- and post-operative external ventricular drainage, degree of hydrocephalus, extent of resection, perioperative complications, and pathological diagnosis. The potential risk factors were analyzed by regression models. Results There were 100 patients (41 females and 59 males) with mean age at time of surgery of 8 years. Ventriculoperitoneal shunt was required in 23 (23%) patients. Univariate logistic regression models revealed a below-near-total resection as the only risk factor. (RR 3.65, 95% CI 1.17–11.37; P= 0.03). Conclusions Prevalence of ventriculoperitoneal shunt after surgery is 23%. Below near-total tumor resection is significant risk factor for postoperative ventriculoperitoneal shunt.